2020
DOI: 10.1021/acsabm.0c00354
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin-Coated Radioluminescent Particles for Radiation-Induced Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) has shown potential as a cancer treatment modality, but its clinical application is limited due to its visible-light activation since visible wavelengths of light cannot penetrate tissues well. Additionally, combination therapies utilizing PDT and radiotherapy have shown clinical promise in several cancers but are limited again by light penetration and the need for selective photosensitization of the treatment area. Herein, we report the development of bilirubin-photodynamic nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The final solid was dried overnight in a vacuum oven at room temperature. The mean diameter of CWO NPs was measured to be approximately 33 nm by transmission electron microscopy (TEM). , …”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final solid was dried overnight in a vacuum oven at room temperature. The mean diameter of CWO NPs was measured to be approximately 33 nm by transmission electron microscopy (TEM). , …”
Section: Experimental Methodsmentioning
confidence: 99%
“…For example, chemotherapeutic drugs, such as paclitaxel, have been extensively studied in the context of polymeric NP encapsulations . Furthermore, significant research has been conducted to study the potential of inorganic materials such as gold, silver, iron oxide, and calcium tungstate (CaWO 4 or CWO for short) NPs in biomedical imaging and treatment applications. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some semiconductor nanomaterials containing high-Z elements also show their potential in radiosensitization, among which alkaline earth metal tungstates are representative nanosensitizers [91]. Jo et al confirmed the radiosensitization effect of CaWO 4 NPs both in vitro (head and neck cancer cells) and in vivo (xenografts) [92].…”
Section: Metal-based Semiconductorsmentioning
confidence: 99%
“…Diverse radiation-sensitive materials, including CaWO 4 NPs, SrAl 2 O 4 :Eu 2+ NPs, Cu NPs, Au nanorods, and Au 8 nanocrystals, constructed by mid- or high-Z elements showed potential in X-ray-triggered persistent luminescence-mediated PDT [ 48 , 49 , 50 , 51 , 52 ]. Deng et al proposed a platform using PLGA vesicles to carry PS verteporfin and gold NPs (2–5 nm) together for efficient energy transfer between the PS and Au NPs.…”
Section: Innovative Nanotechnologies To Improve Pdt Treatmentsmentioning
confidence: 99%